Isolation, screening and identification of some sponge - associated bacterial isolates from six marine sponge species of Son Cha coast - Cuong, Pham Viet; Anh, Nguyen Mai; Quyen, Vu Thi; Kim Cuc, Nguyen Thi (Academia Journal of Biology, 2015)
Sponges are known to be a host of diverse microbial community. By culture – dependent method, 2640 sponge - associated bacterial strains from 6 sponge species of Son Cha peninsula have been isolated. The number of bacterial isolates from the sponge Cliona viridis (LC25) and Callyspongia australis (LC26) was higher than that from the other sponge samples. The sponge Agelas dirpar (LC27) had the least number of isolated bacteria. The anti-vibrio activity of 17 choosen isolates had been examinated by well diffusion method. Among 17 tested isolates, only 3 isolates demonstrated growth inhibition activity against both Vibrio parahaemolyticus and Vibrio vulnificus. Isolate LC27cs1 had strongest inhibitory effect against V. parahaemolyticus with zone of clearance of 21.3 mm. By 16S rRNA gene sequencing method, 3 isolates showing  antibacterial activity against both V. parahaemolyticus and V. vulnificus and 5 others that have inhibition zone more than 10 mm have been identified. Most of isolates belong to Bacillus genus (7/8 isolates) and only one isolate LC25cs5 from sponge Cliona viridis was identified to Paenibacillus barengoltzii.